STUDI PEMANFAATAN SALURAN IRIGASI DI DESA PORAME UNTUK PEMBANGKIT LISTRIK TENAGA PICOHIDRO (PLTPH) MENGGUNAKAN GENERATOR SINKRON MAGNET PERMANEN SATU FASE - Adam, Ahmad Antares; Amin, Nurhani; Masarrang, Maryantho; Pirade, Yulius Salu; Arifin, Yusnaini; Bunga, Melki (Foristek, 2025)
Hydropower plants (PLTA), micro-hydro plants (PLTMH), and pico-hydro plants (PLTPH) in Indonesia use generators with excitation systems to generate fields or magnetic field amplifiers. The use of excitation systems in generators has several drawbacks. In the era of technological development, various types of generators have been developed, one of which is the permanent magnet generator. The Permanent Magnet Synchronous Generator (PMSG) has separate excitation from the synchronous generator and is carried out by permanent magnets to generate the magnetic field instead of coils. This research aims to explore the potential of irrigation channels being utilized as PLTPH using permanent magnet generators. The research method used is the experimental method. The experimental research method is a true experimental method where the equipment is tested and examined. Experimentation involves observation under artificial conditions, where these conditions are created and controlled by the researcher. This study shows that the irrigation channel in Porame Village has the potential to be used as a Pico-Hydro Power Plant (PLTPH) to provide electrical energy as an alternative lighting source, especially at night and during power outages from the national electricity grid (PLN). From the measurement and calculation results, the water flow rate at night is 0.3835 m³/s, with the water power being Pair = 1,901 watts. The type of turbine used is a crossflow turbine, utilizing a permanent magnet synchronous generator.